2082. HIV Pre-Exposure Prophylaxis Practices and Beliefs in Four African Countries. (15th December 2022) - Shah, Neha; Dear, Nicole; Cavanaugh, Joseph S; Iroezindu, Michael; Bahemana, Emmanuel; Kibuuka, Hannah; Owuoth, John; Maswaii, Jonah; Sing'oei, Valentine; Crowell, Trevor A; Parikh, Ajay; Esber, Allahna; et al.
Abstract: Background: Pre-exposure prophylaxis (PrEP) is an essential component to stopping the HIV epidemic. Recent breakthroughs in PrEP including the vaginal ring and long-acting preparations provide more options for individuals. However, PrEP uptake continues to be a challenge. We evaluated PrEP awareness and barriers to PrEP uptake among individuals in four sub-Saharan African countries. Methods: Individuals aged 16 years or older without HIV were referred to the African Cohort Study (AFRICOS) at 12 PEPFAR-supported clinics in Uganda, Kenya, Tanzania and Nigeria through their sexual partners, social media outlets or outreach to communities and schools. Starting in 2020, participants were administered a survey regarding PrEP knowledge, practices, and beliefs every six months. We conducted descriptive analyses from a participant's first study visit after PrEP-related questions had been introduced. Results: From February 2020 to November 2021, the PrEP survey was completed by 372 participants, of whom 204 (55%) were female; their median age was 37.5 (interquartile range (IQR): 26.6-46.5) years old; 228 (61%) were married; 64 (17%) consumed alcohol and 6 (2%) used recreational drugs. Of the 314 (92%) who reported ever having sex, the median age at sexual debut was 18 (IQR: 16-19); 241 (77%) reported 1 regular partner; 295 (94%) had no casual partners in the past six months, 97 (31%) had an HIV+ partner and 26 (10%) had a partner with an unknown HIV status. Results from the PrEP survey are in the Figure. When asked about PrEP, 44 (29%) had discussed PrEP with their provider and 73 (20%) stated they would feel ashamed or embarrassed taking PrEP. Those who had heard of PrEP were more likely to be unmarried (p=0.046) and more likely not to have used a condom during the last sexual encounter with their regular partner (p< 0.05). PrEP knowledge and practices Conclusion: In our cohort, few participants had heard of or were taking PrEP. While our cohort may not represent a high-risk population, PrEP awareness was limited among those who were either unaware of their partner's status or who had a partner infected with HIV. The lack of PrEP awareness highlights the need for increased provider education and outreach especially as new, and potentially less stigmatizing, PrEP options come to market. Disclosures: All Authors : No reported disclosures.